The company and the different forms of outsourced work in Colombia (Encuentros, 2023)
The present work result of research aims to demonstrate that the so-called outsourced contracting, harms the rights of workers in Colombia. Companies, in the contemporary context, have created or promotedvarious forms of work. Outsourced contracting with temporary service companies in Colombia is one ofthe aforementioned forms. These companies were created with the purpose of contracting with third partybeneficiaries, to temporarily collaborate in the development of their activity. However, at the time of the execution of its corporate purpose, the purpose of the creation of the aforementioned companies is not really known. It is perceived, then, that the so-called labor outsourcing brings with it the violation of the principles and rights of workers. This, because the guarantees established by legal and constitutional mandate, are being ignored. It is pertinent to point out that the International Labor Organization (OIT), through the International Agreements ratified by Colombia, has made reference to the subject matter of this investigation, with the purpose of counteracting any form of labor outsourcing. The foregoing, to guarantee equal and dignified treatment to the company’s workers, who may be victims of this type of conduct or phenomenon. Thus, the Colombian State, in its model of social State of law and guarantor ofhuman rights, warns that any mechanism that harms people’s working conditions is prohibited. All because labor relations linked to labor law are within the structure of social and human rights. To demonstratewhat was initially stated, this research is based on the qualitative research approach, with an exploratoryscope. The method used was the critical and analogical hermeneutic.
Keywords: outsourcing, business, labor relations, temporary services and de-employment.